2015
DOI: 10.1007/s00281-015-0505-5
|View full text |Cite
|
Sign up to set email alerts
|

Vasculopathy in scleroderma

Abstract: Systemic sclerosis (SSc) is a multisystem connective tissue disorder featured by vascular injury and fibrosis of the skin and various internal organs with autoimmune background. Although the pathogenesis of SSc still remains elusive, it is generally accepted that initial vascular injury due to autoimmunity and/or environmental factors causes structural and functional abnormalities of vasculature which eventually result in the constitutive activation of fibroblasts in various organs. Structural alterations cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
169
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(176 citation statements)
references
References 118 publications
5
169
0
2
Order By: Relevance
“…Considering the critical role of pericyte loss for the development of the histological and functional vascular changes characteristic of SSc vasculopathy, such as arteriolar stenosis, capillary dilation, and vascular permeability (Asano and Sato, 2015), glycyrrhizin may exert a disease-modifying effect on SSc vasculopathy by restoring pericyte coverage. To address this issue, we looked at the effect of glycyrrhizin on the vascular phenotype of Fli1 ECKO mice, which recapitulate SSc vasculopathy because of the loss of pericyte coverage (Asano et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the critical role of pericyte loss for the development of the histological and functional vascular changes characteristic of SSc vasculopathy, such as arteriolar stenosis, capillary dilation, and vascular permeability (Asano and Sato, 2015), glycyrrhizin may exert a disease-modifying effect on SSc vasculopathy by restoring pericyte coverage. To address this issue, we looked at the effect of glycyrrhizin on the vascular phenotype of Fli1 ECKO mice, which recapitulate SSc vasculopathy because of the loss of pericyte coverage (Asano et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…SSc vasculopathy is marked by specific structural and functional abnormalities (1). The structural changes of SSc vasculature are largely attributable to vascular instability closely related to the altered phenotype of mural cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we also demonstrated that Th1-skewed immune polarization in BLM-treated Irf5 −/− mice is linked to IRF5 binding to the Tbet promoter, suggesting that IRF5 directly suppresses Th1 cell differentiation. Given that IRF5's occupancy of the Tbet promoter was decreased in Tlr4 −/− CD4 + T cells, the activation of TLR4-IRF5 axis promotes a Th2/Th17-predominant inflammatory condition through the direct suppression of Th1 cell differentiation, which may be characteristic of SSc (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A current hypothesis for SSc pathogenesis posits that unknown etiologic factors in a genetically receptive host [4048] trigger microvascular injury characterized by structural and functional endothelial cell abnormalities [4951]. These abnormalities result in the increased production and release of numerous and potent signaling molecules including cytokines, chemokines, polypeptide growth factors, and reactive oxygen species.…”
Section: Pathophysiologymentioning
confidence: 99%